ECONOMIC POLICY AND THE HISTORY OF ECONOMIC THOUGHT - Drakopoulos, S. A. (Stavros A.), 1962-; Katselidis, Ioannis ([S.l.] : ROUTLEDGE, 2023)
This book discusses key issues in economic policy in the context of the history of economic thought. Most of the current and past academic controversies in economics are, explicitly or implicitly, centred around the application and form of economic policy. This is particularly evident in the post-WWII period, with the appearance of economic policy as a distinguishable subfield, but important elements of various economic policy issues can be found throughout the history of economic thought. This book discusses various topics in economic policy - such as questions over state spending and taxation, income redistribution, and the role of money - with each chapter focusing on a particular period or major school of economic thought ranging from the prehistory' of economics up to the present day. Specific chapters of the volume cover the main schools of economic thought from different national and theoretical traditions, incorporating mercantilism, the Physiocratic School, the German Historical School, Marxism, the Austrian School, institutional economics, Keynesian economics, behavioural economics and more. This book will be of great interest to readers of the history of economic policy as well as the history of economic thought, macroeconomics and economic history more broadly.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General; POLITICAL SCIENCE / Public Policy / Economic Policy; Economic policy; Economics -- History